2003
DOI: 10.1210/jc.2003-030220
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Circularly Polarized 50-Hz Magnetic Fields of 200–300 μT Does Not Affect the Pattern of Melatonin Secretion in Young Men

Abstract: Environmental exposure to time-varying (alternating current) magnetic fields (MFs) produced by electrical current flow is a perceived public health risk. Several epidemiological studies report correlations between MF exposure and carcinogenesis. It has been hypothesized that MF-induced suppression of melatonin could provide the mechanism by which this effect is mediated. Here, we describe results from a controlled laboratory-based study designed to detect changes in human melatonin secretion after a 2-h exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Another issue is the control fields to which volunteers were exposed. For example, Warman et al [2003b] employed acute exposes up to 300 mT and found no real evidence of melatonin disruption. However, their control level is given as <0.2 mT, which could be seen as the region where chronic exposure still results in nocturnal melatonin suppression.…”
Section: Discussion Melatonin Suppression By Magnetic Fieldsmentioning
confidence: 99%
“…Another issue is the control fields to which volunteers were exposed. For example, Warman et al [2003b] employed acute exposes up to 300 mT and found no real evidence of melatonin disruption. However, their control level is given as <0.2 mT, which could be seen as the region where chronic exposure still results in nocturnal melatonin suppression.…”
Section: Discussion Melatonin Suppression By Magnetic Fieldsmentioning
confidence: 99%
“…They added that, unlike light exposure, the potential neuroanatomical pathways for melatonin suppression due to magnetic field exposure remain obscure. Warman et al (2003a) reported that their study into the effects of 200-300 lT magnetic fields (50 Hz) showed no effect on melatonin suppression or circadian rhythm phase-shift.…”
Section: Anthropogenic Electric and Magnetic Fieldsmentioning
confidence: 99%
“…Experimental manipulation of Earth-strength magnetic fields as well as exposure to magnetic fields (MFs) associated with the 50/60 Hz electric power distribution system have been shown to suppress melatonin production in some, but not all, studies (Warman et al 2003a;Phillips and Deutschlander 1997;Reiter 1994). Light exposure may be critical for MF-induced melatonin suppression and it also modifies the ability of certain species to derive compass information from the Earth's magnetic field (Phillips and Deutschlander 1997).…”
Section: The Role Of Melatoninmentioning
confidence: 99%
See 2 more Smart Citations